Penentuan Nilai Work Level Month (WLM) Maksimum Pekerja Pada Ruangan Berbahan Gipsum - Setiono, Made Budi; Sutapa, Ngurah; Sudarsan, I Wayan Balik (Universitas Hamzanwadi, 2019)
Research has been done to identify radioactive elements and determine Work Level Month (WLM) values on workers in the sized room of 2m x 2m using gypsum material. Identification of radioactive elements in gipsum samples using Laser Induced Breakdown Spectroscopy (LIBS) methods and measurement of radiation dose in gypsum walls using surveymeter methods. Identification of radioactive elements to the LIBS method showed an element of Th, U, K were detected. The accumulated dose of radiation detected in the room using gypsum walls is (1,6993±0,0169) μSv and the accumulated dose of radiation detected in the room without gypsum walls is (0,5657±0,0292) μSv. WLM values from the room use a gypsum walls if workers work for 1 years is 0,9924 WLM, then it is still considered safe because it is still below the RR values that has been determined that is equal to 50 WLM.